Membangun Front End Website E-Commerce Dengan Menggunakan Framework Bootstrap 4 Dan Codeigniter 3 - Bagus Arinata; I Nyoman Yudi Anggara (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2020)
As time goes by, technology goes very fast. Many business people use technology, one of which is an e-commerce website. E-commerce websites are very good to use because they can reach and be accessed by many people. Therefore the web design must be well made. In website design, the thing that must be considered is the user interface which is one of the factors that can determine the increase in website traffic. The better and simpler the user experience, neater, innovative, creative, and attractive the user interface is made, the more interested the user will be in exploring the website. This study aims to create an e-commerce website front end using the bootstrap 4 and codeigniter 3 framework.